Virtual education and academic motivation in university students - Sosa-Gutierrez, Fredy (2024)
In the state of confinement due to COVID-19, universities operated virtually, ignoring the level of motivation of their students. The objective of the research was to determine the relationship between virtual education and academic motivation in university students, at the same time identifying the link of the first variable with intrinsic and extrinsic motivation and the strategies used by the teacher. Its approach is quantitative, non-experimental design and correlational type. The sample is 192 university students. The technique was the survey and questionnaire instruments. The Pearson correlation statistical test showed a relationship of r = 0.8704, considering a range -1 <= r <= 1 and the coefficient determined between the variables are in a positive interval r <= 1. Concluding that there is a direct positive relationship with a value 0.9 close to 1. The greater the learning resources, support, and virtual collaboration, the higher the academic motivation of young students.